The Transmission History of 2 Kings 21:13b - Brown-deVost, Bronson (2019)
In an odd turn of phrase, the Masoretic tradition of 2 Kings 21:13b likens Jerusalem’s destruction to the wiping of a bowl or dish. This reading has almost universally been accepted in modern scholarship, with virtually no attention given to the significant variants in the other biblical versions. An analysis of these variants suggests a complex transmission history of this passage that has been profoundly shaped by a rich culture of interpretation within a dynamic sociolinguistic context.
Keywords: Bibel; 2 Kings 21:13; Jerusalem; biblical versions; bowl; Destruction; tablet